2011
DOI: 10.1158/1055-9965.epi-11-0465
|View full text |Cite
|
Sign up to set email alerts
|

Parity and Lactation in Relation to Estrogen Receptor Negative Breast Cancer in African American Women

Abstract: Background Estrogen receptor (ER) negative, progesterone receptor (PR) negative breast tumors occur more commonly in women of African ancestry. Recent research indicates that the effects of reproductive factors may differ by hormone receptor status. We assessed the relation of parity and lactation to incidence of ER−/PR− and ER+/PR+ breast cancer in a cohort of African American women. Methods From 1995–2009, 457 incident cases of ER+/PR+ and 318 cases of ER−/PR− breast cancer were confirmed by review of path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
128
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 135 publications
(156 citation statements)
references
References 48 publications
22
128
2
4
Order By: Relevance
“…In another large study of African American women, breastfeeding was found to be a protective factor against hormone receptor-negative phenotypes [37]. Again, breastfeeding was less common among African American women than other ethnicities [37]. This low rate of breast feeding may indicate a cultural distinction between African American populations and populations of other heritage in the United States.…”
Section: Hormonal Factorsmentioning
confidence: 97%
See 4 more Smart Citations
“…In another large study of African American women, breastfeeding was found to be a protective factor against hormone receptor-negative phenotypes [37]. Again, breastfeeding was less common among African American women than other ethnicities [37]. This low rate of breast feeding may indicate a cultural distinction between African American populations and populations of other heritage in the United States.…”
Section: Hormonal Factorsmentioning
confidence: 97%
“…An inverse association has been found for length of duration of breastfeeding and risk for developing triple-negative breast cancer [11,12,15,[37][38][39]. In several studies, this reduced risk was found among women who breastfed for a duration of greater than four months [11,12].…”
Section: Hormonal Factorsmentioning
confidence: 99%
See 3 more Smart Citations